Determinants of Agripreneurial Career Intentions: Evidence From Agriculture Students - Suprehatin; Muhammad Rasyid Shidiq (School of Business, Bogor Agricultural University (SB-IPB), 2020)
The participation of young people in agriculture is essential for addressing issues of food security, youth unemployment, ageing farmers, and the digital revolution in the agriculture and food sectors. Various programs have been conducted by the Government of Indonesia (including One Million Millennial Farmers Movement Program), by the private sector, and by universities to raise the interest of students and increase the number of young farmers in the agricultural and food industry. These programs are a response to the continuing decline in the number of Indonesian farm households and the need to attract younger entrants into the industry. This study analyses the factors that influence the intention of agricultural students to become agripreneurs using a modified theory of planned behaviour (TPB) approach. Data obtained from a survey of 204 agricultural students at IPB University using a voluntary sampling method and analysed using partial least squares structural equation modelling (PLS SEM). The results showed that individual characteristics, attitudes, subjective norms, and perceived behavioural control of agricultural students had a significant effect on the intention to become an agripreneur. The study also showed that family background did not significantly influence the intention of agricultural university students to become an agripreneur. The findings contribute to the literature by providing a better understanding of the role that agriculture education and training plays in increasing students’ intention to work in agriculture. Keywords: agriculture education, agripreneur, agripreneurship, intention, youth farmer